Min egen reise fra kunstnerisk praksis til forskning : – med autoetnografi som forskningsmetode - Haaland, Agnete G. (Teatervitenskapelige studier, 2025)
In "My journey from artistic work to artistic research" I explore differences and similarities between artistic and academic research seen from my perspective as a Norwegian actress. As a practitioner researcher I have used autoethnography to place myself and my own experiences as an actress and artistic director into an academic context in several previous academic articles. In the present article, I seek to define the differences between art and research based on my own material, and I explore how performing arts can become artistic research. I also include the methodology developed by OECD in the Frascati Manual to define research. By doing so I detect how theatre directors, actors and acting teachers like Konstantin Stanislavski used autoethnography as a method long before it was recognised as an academic theory.